Evaluation of the Bacterial Infections and Antibiotic Prescribing Practices in the Intensive Care Unit of a Clinical Hospital in Romania - Sándor Szabó; Bogdan Feier; Alina Mărginean; Andra-Elena Dumitrana; Simona Ligia Costin; Cecilia Cristea; Sorana D. Bolboacă (Antibiotics)
Introduction: Healthcare-associated infections (HAIs) are associated with increased mortality, antimicrobial resistance, and high antibiotic use. Methods: The characteristics of bacterial resistance and antibiotic consumption in the intensive care unit (ICU) of a clinical hospital in Romania were evaluated. Demographic data of patients, identified bacteria, antibiotics administered, and their sensitivity profiles were collected and analyzed. Results: One hundred and twenty-five patients, with a median age of 68 years, mostly male (60%), were included in the study. More than one-third of the patients died. The deceased patients were older (median age of 74 years), had longer hospitalization (median of 9 days) and bacteria detected (55.3%), and had higher antibiotic consumption than the discharged patients. The most frequent bacteria identified in our cohort were Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa in deceased patients and Klebsiella pneumoniae, Escherichia coli, Staphylococcus hemolyticus, and Enterococcus faecalis in the survived group. The top three antibiotics used were ceftriaxone, metronidazole, and meropenem. Resistance to antibiotics was observed in 44.3% of the deceased group and 37.5% of patients who were discharged (χ2 = 5.5, p = 0.0628). Discussion: A positive monotonic association was observed between the number of hospitalization days and the number of antibiotic doses, with a higher correlation coefficient for deceased patients (0.6327, p < 0.0001) than in survived group (0.4749, p < 0.0001). Conclusions and Future Trends: This study provides a real picture of HAIs, the characteristics of bacteria, and the consumption of antibiotics in an ICU of a clinical hospital in Romania. The data obtained are similar to those from other international studies, but further studies are needed to reflect the real situation in Romania.